Combined Effect of Resting Time and NaHCO3 on Solubility and Gel Properties of Low-Salt Chicken Myofibrillar Protein - Wan-Li Cheng; Peng-Lei Yao; Xue-Hua Zhang; Yan-Yan Zhao; Sheng-Ming Zhao; Zhuang-Li Kang (Foods)
To investigate the interaction effects of resting times (0, 6, and 12 h) and NaHCO3 concentrations (0, 2, 4, and 6 g/kg) on chicken myofibrillar protein (CMP), this study analyzed the changes in solubility, active sulfhydryl groups, rheological behavior, fluorescence, and gel properties of CMP solutions (60 mg/mL). The results indicated that pH significantly increased with higher NaHCO3 concentrations and longer resting times. Consequently, solubility, active sulfhydryl groups, apparent viscosity, shear stress, G’ value at 80 °C, hardness, springiness, and cohesiveness all significantly increased, while particle size, turbidity, and whiteness significantly decreased. However, these trends were not observed in samples treated with an amount of 6 g/kg NaHCO3 and/or a resting time of 12 h. The findings suggest that treatment with 4 g/kg NaHCO3 and a resting time of 6 h effectively reduced protein aggregation and enhanced solubility. Conversely, excessive NaHCO3 or prolonged resting times resulted in decreased protein solubility and deteriorated textural properties.